A Strengths, Weaknesses, Opportunities, and Threats Analysis of Chatbot Rimba as an Educational Technology Innovation for Ecosystem Learning in Islamic Primary Schools in Pontianak City - Vidya Setyaningrum; Roikhatul Janah; Ghafriyadi; Farninda Aditya (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
Schools, as the spearhead of education, have a responsibility to implement local cultural values in the learning process. This study examines the development and feasibility of chatbot Rimba, an AI-based digital learning medium designed to support ecosystem learning and strengthen local cultural values among elementary school students in West Kalimantan. Using a quantitative descriptive approach, data were collected through expert validation questionnaires and student response surveys administered to fifth-grade students at four State Islamic Elementary Schools (MIN 1–4) in Pontianak City during the 2024/2025 academic year. Validation data were analyzed using Gregory’s technique, the results show that Chatbot Rimba achieved a content validity index (CVI) of 1.00 across material, software, and language aspects, indicating strong relevance in all categories. Student response data further demonstrate highly positive evaluations, with an overall mean score of 4.63, categorized as excellent. The highest ratings were found in usability, followed by appearance and content, confirming the media’s clarity, accessibility, and engaging design. This study concludes that Rimba chatbot is an effective AI-based learning tool for ecosystem education in West Kalimantan elementary schools, receiving positive feedback from experts and students. SWOT analysis highlights its potential to enhance learning, foster local-culture-based character education, and support academic achievement, though further technical improvements are needed.